Black Sea Energy Resource Development and Hydrogen Energy Problems - Veziro; Tsitskishvili, Marat. (NATO Science for Peace and Security Series C: Environmental Security, 2013)
NATO Advanced Research Workshop The Black Sea: Strategy for Addressing its Energy Resource Development and Hydrogen Energy Problems was held in order to evaluate the Black Sea Regions environment, discuss the ways and means of protecting it, and to evaluate the methods of production of the energy carrier, hydrogen. Papers presented at the workshop, proposed various methods of hydrogen production from the hydrogen sulfide, from marine macro algae and other bacteria, storage and utilization of hydrogen, oil spills and pollutants in the Black Sea, degradation of the sea and the land around the region, and ways and means of protecting the environment. The workshop participants unanimously expressed the need to establish close cooperation amongst the Regions countries regarding the development of its energy resources, and at the same time protecting its environment. These recommendations have been put together in the Batumi Manifesto. This book entitled Black Sea Energy Resource Development and Hydrogen Energy Problems puts together the papers presented at the workshop, starting with the Batumi Manifesto. This valuable volume should be in the libraries of all the scientists, engineers, environmentalists, economists and decision makers involved in the development of the Black Sea Region and in the introduction of clean and abundant Hydrogen Energy.